PARIWISATA DAN KEMISKJNAN DI BALI - I Gusti Ngurah Agung Suprastayasa (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2007)
The Tourism industry in Bali makes important contributions to the economies of Bali as well as Indonesia, particularly to foreign exchange earnings, employment and GDP. However, the vast growth of tourism industry has not been able to eradicate poverty. Some measures should be made to make tourism generates more benefit to the poor. The private sector, community, Non-Government Organizations and governments should